The Learning Strategy for Indonesian Grammar: Students’ Perspective on Indonesian Language for Foreign Speakers - Fida Pangesti; Arti Prihatini; Fauzan (Universitas Pendidikan Ganesha, 2023)
Foreign students face challenges in Indonesian language learning, especially grammar. Thus, they can use grammar learning strategies to understand grammar. However, research on grammar learning strategies from BIPA students’ points of view is still limited. In filling this gap, this study aims to analyze (1) strategies for learning Indonesian grammar for BIPA students and (2) the pedagogical implications of learning strategies for grammar for BIPA students. This research is a quantitative descriptive case study. The quantitative data were obtained from Grammar Learning Strategies (GLS) questionnaire. Furthermore, verbal data from respondents was obtained from semi-structured interviews. The research participants were 30 foreign students (BIPA students). Data were analyzed by using Likert-scale descriptive statistics and qualitative analysis consisting of transcription, codification, interpretation, validation, and drawing conclusions. This study found that the strategy most frequently used by BIPA students was social strategy (mean=4.28), followed respectively by metacognitive strategy (mean=4.15), cognitive strategy (mean=4.13), and affective strategy (mean=3.37). The pedagogical implication was that grammar learning needs to be designed by a contextual-communicative approach so that it can accommodate the preference of BIPA students’ learning strategies.